Strategic Analysis and Choice - Warner, Alfred G (Business Expert Press, 2010)
Ebook from IG Library ; Strategy and strategic planning at the firm level often gets a bad reputation because managers aren’t trained in it and the tools are unfamiliar, infrequently used and often poorly applied. The outcomes of these efforts can therefore be incomplete, biased, and far too subjective and the results disappointing.